APPLICATION OF MORSE CODE USING MACROMEDIA FLASH MX - Setyo Ariyanto; Susi Wagiyati P, SKom, MMSI (Jurnal Sistem Informasi, 2003)
Communication system currently has an important role for all aspects, both in the field of security, tracking, and reporting, as well as any other field. For media submission of this communication can be a sound, or light rays, as well as written form. In this case the authors use the communication form of morse code via Macromedia Flash MX contained the personal computer (PC). The development of technology for the design and manufacture as well as interactive applications animation been presented by many leading vendors. Macromedia Flash is one means of creating interactive animation. To better satisfy the user, design, color and animation games are elements that need to be taken into account in making animation applications. So the application of science graphic design and application programs become the main thing in making the application. Realizing that the future world of information and communication is very important, then the scientific writing is the writer trying to build an application with the skills animation using Macromedia Flash MX Application Passwords are Morse.